Desarrollo de un sistema experto para el área de riesgos de trabajo del Instituto Ecuatoriano de Seguridad Social de Loja, para la planificación de inspecciones en empresas e instituciones. - Imacaña Fernández, Jenny Paulina (2014)
In the present degree work has been developed SPEEARTIESS Expert System to optimize the verifier activities of the Area Occupational Hazards IESS in Loja to develop them and achieve them quickly, and effectively opportune for verification or inspection performed at the business generates as a percentage score and is based on a checklist containing the regulations established by the Ecuadorian Institute of Social Security. The methodology is the methodology proposed by Weiss and Kulikowski, which adapts to the needs of the expert system and allows the implementation of these modules that address the design and implementation phases. These phases allow having a well-structured program that answer the user requirements. The Expert System development has been done using Java programming language using the NetBeans IDE platform providing the necessary tools for implementing programs on multiple platforms, in addition to resources for developers who offer different libraries based on this technology. As manager of the MySQL database and structuring the Expert System were used rules regulations checklist and inference engine for file usage Assessment report. ARFF containing values that are the weights of each question and for the module Learning Multilayer Perceptron algorithm based on neuronal networks for the obtention of results in evaluation or verification. For the testing process was used JUNIT tool in order to verify, manage and execute a set of automated tests was used, also conducted a series of acceptance tests and surveys applied to allow the Survey Verifier to validate and verify all Expert System requirements.